C Programming in Linux - Haskins, David (BookBoon, 2011)
Using a series of web development examples, this book will give you an interesting glimpse into a powerful lower-level world. C is tight and spare and economical, and in the current world climate people who know C will ensure critical systems keep running. A knowledge of C is now and has been for years a pre-requisite for serious software professionals and with the recent popularity and maturity of Open Systems this is even more true.